Determination of heavy metals in soil and biomass by the application of potentiometric stripping analysis - Dragan M. Stević; Ignjatović Ivana Sredović (Zaštita Materijala)
In this paper the determination of lead, cadmium and zinc in soil and biomass was performed using potentiometric stripping analysis (PSA). In order to establish the optimal experimental conditions for PSA of Pb, Cd and Zn, the influence of pH value, time of metals extraction, stirring rate of the solution and the thickness of the mercury layer, as the working electrode, was investigated. The influence of mentioned parameters was tested for individual and simultaneous metals determination. The achieved limits of determination of single ions were for: lead 22.5 μg dm-3, cadmium 16.2 μg dm-3 and zinc 18.8 μg dm-3. The obtained results deviated from the expected for 1.1%, 1.9% and 1.8%, for lead, cadmium and zinc, respectively. For simultaneous determination, the method is tested using the ions contents as follows: 45.0 μg dm-3 for lead, 32.5 μg dm-3 for cadmium and 37.5 μg dm-3 for zinc. The relative errors for simultaneous determination were: 4.6% for lead, 1.9% for cadmium and 1.9% for zinc. For the established optimal conditions, except for lead, deviations did not exceed ±2%. It is shown that potentiometric stripping analysis is usable for individual and simultaneous determination of lead, cadmium and zinc in soil and biomass.